Development of a novel non-targeted analytical method on evaluating the thermal stability of pesticides, enabling the identification of degradation products - Florian Dubocq; Roua Bou Orm; Pierre L’Yvonnet; Xavier Sarda; Gaelle Vial; Arnaud Duboisset; Benjamin Carbonnier; Julien Parinet (Exploration of Foods and Foodomics)
Aim: The present work aims to propose an alternative analytical protocol for assessing the thermal stability of plant protection products between 90°C and 240°C. In that view, this work seeks to identify any degradation products that may be overlooked during regulatory hydrolysis studies. Thus, we evaluate if a new regulatory approach is necessary and how this could be done by academic research. This requires working under similar conditions. Methods: A comprehensive analytical workflow was designed and implemented for ten active substances to study and investigate their overall degradation behaviour and volatilisation. The results were then compared with those reported in the regulatory studies. Results: The ratio of detected degradation products to active substances ranged from 0.5% to 50%. Volatilization products were identified for all compounds analyzed using TGA-GC-MS. This confirmed the pattern of degradation followed by volatilisation, except for tetraconazole, which volatilises before degradation. Some of the detected compounds were not reported at all in regulatory studies, or were detected at higher concentrations, such as IN-EQW78 and 500M07. Conclusions: This study confirmed the feasibility of conducting thermodegradation studies without relying on radiolabelled substances. It also identified two overlooked products and emphasised the importance of conducting studies exceeding 120°C.